2018
DOI: 10.1073/pnas.1811024115
|View full text |Cite
|
Sign up to set email alerts
|

Engineering selectivity into RGK GTPase inhibition of voltage-dependent calcium channels

Abstract: SignificanceInflux of calcium ions through surface membrane calcium channels that open in response to electrical signals is important for vital biological processes including generation of the heartbeat and nerve cell communication. Blocking such calcium channels in a tissue- and isoform-specific manner is a sought-after treatment strategy for diseases including chronic pain and Parkinson’s disease. Proteins that can be expressed in cells to selectively block different calcium channel types have particular adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…2010; Puckerin et al . 2018). A recent elegant study revealed that endogenous Rad in cardiomyocytes constitutively exerts a gating brake on a fraction of Ca V 1.2 channels.…”
Section: Voltage‐gated Calcium Channels: Basic Structure Function Anmentioning
confidence: 99%
See 4 more Smart Citations
“…2010; Puckerin et al . 2018). A recent elegant study revealed that endogenous Rad in cardiomyocytes constitutively exerts a gating brake on a fraction of Ca V 1.2 channels.…”
Section: Voltage‐gated Calcium Channels: Basic Structure Function Anmentioning
confidence: 99%
“…2012; Puckerin et al . 2016, 2018). In the particular case of Rem inhibition of Ca V 1.2, the β‐binding‐independent mechanism of inhibition is mediated by an interaction of the Rem distal C‐terminus with the α 1C N‐terminus region just upstream of the first transmembrane spanning segment of the channel (Yang et al .…”
Section: Voltage‐gated Calcium Channels: Basic Structure Function Anmentioning
confidence: 99%
See 3 more Smart Citations